Developing an Innovative Digital Storybook to Improve the Fifth Grade Students' Reading Comprehension - Amni, Laila; Ani Fiani; Dewi Syafitri (Universitas Sarjanawiyata Tamansiswa, 2025)
Abstract: The aim of this study was to find out the validity and practicality of the developed digital storybook to improve fifth-grade students' reading comprehensic The development research based on the ADDIE model consisting of analysis, desig development, implementation, and evaluation was used in developing the produ There were 3 experts reviewing the product in the expert review, 3 students involv in the one-to-one evaluation and 9 students in the small group evaluation. To colle the data, validation sheets, student questionnaires and interviews were used. T collected data were analyzed qualitatively for the interviews and quantitatively usi average scores and percentages. The developed product was valid after bei evaluated by experts in terms of content, instructional design, and layout, with average score of 4.07, categorized as highly valid. The product was also practic with an average score of 4.67 in the one-to-one evaluation and 4.40 in the sm group evaluation, categorized as very highly practical. In conclusion, the develop digital storybook were valid and practical in improving students' readi comprehension.Keywords: ADDIE model, digital storybook, reading comprehension, research and development.